PERSEPSI GURU TERHADAP IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BIOLOGI SMA DI KABUPATEN OGAN ILIR - Kumala, Diana; Hidayat, Saleh; Saputri, Wulandari; Astriani, Meli; Suhartati, Suhartati (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
This study aims to describe teachers' perceptions of the implementation of the independent curriculum in biology learning activities in Ogan Ilir District. The method used is the descriptive-qualitative method. The research sample consisted of eight biology teachers in four high schools (SMA) in Ogan Ilir District who had implemented the independent curriculum. Data on teacher perceptions were obtained through observation and interviews using observation sheet instruments, interview instrument grids, and interview instrument question sheets. The collected data was then analyzed with a qualitative descriptive analysis. The results showed that all participants had good perceptions regarding the implementation of the independent curriculum in schools and acknowledged the advantages contained in the independent curriculum, but only some of the participants were able to consistently apply it in learning activities. This is because participants experience difficulties in designing independent curriculum teaching modules, compiling assessments, implementing learning models, using independent teaching platforms, and preparing intracurricular reports and P5 report cards. These findings indicate that socialization and training on the independent curriculum need to be maximized again by including consistent mentoring programs for teachers so that they can consistently implement the independent curriculum in the teaching and learning process.